American Intervention In The Overthrow Of President Ferdinand E. Marcos In Philippines In 1983-1986 - Anggara S, Clip; Marjono, Marjono; Swastika, Kayan (JURNAL HISTORICA, 2017)
American intervention in the government of President Ferdinand E. Marcos related to the economic crisis, political, social in Philippines. The development of communist ideology supports the growing crisis in the Philippines and it influences the interests of America that related to the economic and politics in both countries. The purpose of this study is to provide new knowledge about the politics in Southeast Asia with America around the 20th century, especially the leadership of Ferdinand E. Marcos in Philippines. This study applies the method of historical research with a heuristics technique or a source selection, a source criticism, an interpretation, and historiography. American intervention overthrows the power of Ferdinand E. Marcos through the military field and political field. America utilizes a conspiracy between the high officials RAM (Reform the Army Movement), the diplomacy senator from the part of President Reagan to the government of Philippines, and support to the opposition under Cory Aquino. Finally, American intervention managed to depose Marcos from the presidency which is later replaced by Cory Aquino in 1986. Keywords: American intervention, President Ferdinand E. Marcos, and Filipina